Melatonin Promotes Differentiation of Human Spermatogonial Stem Cells Cultured on Three-Dimensional Decellularized Human Testis Matrix - Salem, Maryam; Khadivi, Farnaz; Feizollahi, Narjes; Khodarahmian, Mahshad; Saedi Marghmaleki, Mojtaba; Ayub, Shimal; Chegini, Raziye; Bashiri, Zahra; Abbasi, Yasaman; Naji, Mohammad; et al. (Urology Journal, 2024)
Purpose: The use of 3D (3-Dimensional) culture systems supported cell-to-cell and cell-to-extracellular matrix (ECM) interactions, proliferation, and differentiation of SSCs (Spermatogonial stem cells). The potential advantages of ECM-based scaffolds for in vitro spermatogenesis have been indicated in human and animal experiments. Furthermore, the strong antioxidant and anti-inflammatory activities of melatonin have improved in vitro manipulation of human SSCs in culture conditions. Materials and Methods: SSCs were isolated from the testis of three dead-brain patients and then propagated for four weeks. The characterization of SSC colonies was done using real-time PCR (Polymerase chain reaction), ICC (Immunocytochemistry), and xenotransplantation to mice model. Decellularization of the human testis was performed using 0.3% sodium dodecyl sulfate (SDS) solution and 1% Triton X-100. Also, various characterizations of DTM (Decellularized testicular matrix ) were carried out using histological staining and DNA content analysis. The optimum dose of melatonin was selected by MTT (Methyl thiazol tetrazolium). SSCs were cultured in 4 groups: control, melatonin, ECM, and ECM-melatonin in a differentiation medium for four weeks. The expression of differentiation genes was evaluated by real-time polymerase chain reaction. In addition, the viability of cultured cells was assessed by MTT assay. Results: The results of ICC and real-time PCR showed the expression of undifferentiated SSC markers (PLZF and GRFA1) in SSC colonies following the 2D culture of isolated SSCs. The presence of testicular ECM components after different staining methods; and the reduction of DNA content confirmed the proper decellularization process. Germ cell apoptosis significantly decreased in melatonin and ECM groups, and the higher viability of SSCs was seen in the ECM-melatonin group. The relative expression of GFRA1 and PRM2 decreased and increased in ECM and ECM-melatonin groups, respectively. Conclusion: Our study showed that the addition of melatonin to the human naturally-derived ECM scaffold could provide a suitable platform for inducing the differentiation and preserving the viability of SSCs.